Enhancing the accuracy in diagnosing Peripheral vestibular disorders - Zainun, Zuraida (2010)

(untitled)
Peripheral vestibular disorder (PVD) is serious and common. Clinically, giving an accurate diagnosis of PVD can be challenging. Without the appropriate diagnosis, clinicians are not able to provide proper management for patients. Therefore, this study was conducted to enhance the accuracy in diagnosing PVD by investigating two new tests, i.e. Vestibular evoked myogenic potential (VEMP) and Malay version of vertigo symptom scale (MVVSS) to be compared with the existing vestibular tests, namely caloric test and Dix-Hallpike test (DHT). This study consisted of two parts: pilot (translation and validation of MVVSS and optimization of VEMP protocol) and main study. MVVSS was found to have adequate content, high test reliability and adequate construct validity. An optimal protocol to record VEMP was also achieved. In the main study, 40 normal participants and 65 PVD subjects participated.